Smart Tax – The Concept of Gamification, Board Game & Metaverse Inside Tax Profiling To Make Taxpayers Comfortable - Novianto, Sendi; Gamayanto, Indra; Sundjaja, Arta Moro; Mailangkay, Adele B L (Teknik Informatika Universitas Suryakancana Cianjur, 2024)
Tax is one of the essential pillars in the development of a country, where taxes can have a positive impact on changing people's lives. This research will focus on how gamification, board games, and metaverse can increase the ease of paying taxes, create a more effective and efficient organizational structure to generate business for state financial institutions, implement tax incentives appropriately, and provide fair solutions for taxpayers. Convenience for the community is an essential focus in this research because it is a fundamental thing that must be built and implemented so that when paying taxes, people feel that it is no longer an obligation but a lifestyle. Furthermore, applying technology such as gamification, board games, and metaverse will improve services to the community. Several concepts, such as building a business in a financial institution, will generate profits for the country. Finally, after these things can be implemented, institutions can provide right-on-target incentives to the community that really should get them, including incentives that fall into the correct category. The results of this study are a framework for compiling a smart tax profile (level of maturity in compiling a tax profile) that combines all types of incentives to be used as essential guidelines and applied in the long term. In this conceptual research, gamification is a link with taxpayers to make it more interesting and increase positive bonds; board games are game boards that are useful for carrying out manual simulations by sitting together and discussing, while metaverse and AI can be used for tax simulations so that taxpayers can understand more deeply about taxes.